The silver lining of a mind in the clouds: interesting musings are associated with positive mood while mind-wandering - Franklin, Michael S.; Mrazek, Michael D.; Anderson, Craig L.; Smallwood, Jonathan; Kingstone, Alan; Schooler, Jonathan (Frontiers in Psychology, 2013)
The negative effects of mind-wandering on performance and mood have been widely documented. In a recent well-cited study, Killingsworth and Gilbert (2010) conducted a large experience sampling study revealing that all off-task episodes, regardless of content, have equal to or lower happiness ratings, than on-task episodes. We present data from a similarly implemented experience sampling study with additional mind-wandering content categories. Our results largely conform to those of the Killingsworth and Gilbert (2010) study, with mind-wandering generally being associated with a more negative mood. However, subsequent analyses reveal situations in which a more positive mood is reported after being off-task. Specifically when off-task episodes are rated for interest, the high interest episodes are associated with an increase in positive mood compared to all on-task episodes. These findings both identify a situation in which mind-wandering may have positive effects on mood, and suggest the possible benefits of encouraging individuals to shift their off task musings to the topics they find most engaging.